2019
DOI: 10.29328/journal.cjncp.1001010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and associated factors towards nursing care documentation among nurses in West Gojjam Zone public hospitals, Amhara Ethiopia, 2018

Abstract: Background: In health care systems nursing care documentation is a vital and powerful tool that ensures continuity of care and communication between health personnel for better patient outcomes. Knowledge, attitude and practice of nurses' towards nursing care documentation affect the quality and coordination of patients' care. Hence, this study aimed to assess knowledge, attitude, practice and associated factors towards nursing care documentation among nurses in West Gojjam Zone public hospitals, Amhara Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…As a result, health professionals use standard documentation tools such as manual records and/or electronic systems to document their routine activities correctly and on time while respecting the rules of ethics 21. Accordingly, health professionals’ routine practice documentation was assessed by using 12 ‘yes’ and ‘no’ questions 3 22. The level of health professionals’ routine practice documentation was determined using the mean value as a cut-off point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, health professionals use standard documentation tools such as manual records and/or electronic systems to document their routine activities correctly and on time while respecting the rules of ethics 21. Accordingly, health professionals’ routine practice documentation was assessed by using 12 ‘yes’ and ‘no’ questions 3 22. The level of health professionals’ routine practice documentation was determined using the mean value as a cut-off point.…”
Section: Methodsmentioning
confidence: 99%
“…The tool used was developed based on reviewing similar studies 3 18 22. A pretested, self-administered questionnaire was used.…”
Section: Methodsmentioning
confidence: 99%
“…A structured, self-administered English version questionnaire and chart review tool were adapted from previous similar studies (17,19,21) with six parts or items. Part-I contains eight questions regarding of socio-demographic characteristics of the nurses; Part II ten practice questions for measuring documentation practice with "Likert -type" or responses.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…Inadequate documentation among nurses has been demonstrated to negatively affect patients’ outcomes, treatment decisions, diagnostic methods, the performance of nurses, and the profession as a whole. It is also linked to the issue of omitting prescriptions, which increases the risk of legal harm that involves severe injury or death of a patient ( 6 , 7 ). A study in Bahir Dar, Northwest Ethiopia, revealed that 87.5% of medication administrations have erroneous documentation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researches recommended utilizing a multidisciplinary approach to solve documentation issues. These include developing rules and regulations ( 1 , 7 ) and providing continuing opportunities for nurses to receive training on the effectiveness of documentation ( 2 , 6 , 15 ). It is also expected of nursing leaders to encourage, support, and hire more personnel ( 6 , 15 ).…”
Section: Introductionmentioning
confidence: 99%